All My Relations: Reclaiming the Stories of our Indigenous Grandmothers - Beniuk, Jodi (Atlantis, 2016)
In this paper, I document conversations I engaged in with my Métis grandmother (Grambear) and the process of compiling her teachings into a handmade book. Drawing on theory in the flesh and felt theory, I explore the significance of my grandmother’s teachings for me personally and for Métis women more generally. For me, this project was not only about honouring my grandmother and her stories, but it is also about the process of Indigenous revitalization, resurgence, and decolonization.This paper won the Women’s and Gender Studies et Recherches Féministes (WGSRF) Undergraduate Essay Prize in 2014.